2012
DOI: 10.1097/ta.0b013e318270d2fb
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adaptive statistical iterative reconstruction on radiation dose in evaluation of trauma patients

Abstract: BACKGROUND A recent study showed that computed tomographic (CT) scans contributed 93% of radiation exposure of 177 patients admitted to our Level I trauma center. Adaptive statistical iterative reconstruction (ASIR) is an algorithm that reduces the noise level in reconstructed images and therefore allows the use of less ionizing radiation during CT scans without significantly affecting image quality. ASIR was instituted on all CT scans performed on trauma patients in June 2009. Our objective was to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Similar results were obtained with ASIR by Matsuda et al [18] , who evaluated the value of ASIR in CT porto-venography; they found that ASIR helped reduce the noise and improve the CNR of the liver images and the liver vasculature images. Although the ASIR technique has been shown to enable reduce radiation dose without compromising image quality [19] , to our knowledge, no previous studies have evaluated images to assess the effect of the SK technique compared with the ASIR30% and StK techniques. In our study, the SK technique produced better image quality, quantitatively and qualitatively than the StK technique and similar image quality compared to ASIR30%.…”
Section: Image Noise Image Contrast Artifactsmentioning
confidence: 99%
“…Similar results were obtained with ASIR by Matsuda et al [18] , who evaluated the value of ASIR in CT porto-venography; they found that ASIR helped reduce the noise and improve the CNR of the liver images and the liver vasculature images. Although the ASIR technique has been shown to enable reduce radiation dose without compromising image quality [19] , to our knowledge, no previous studies have evaluated images to assess the effect of the SK technique compared with the ASIR30% and StK techniques. In our study, the SK technique produced better image quality, quantitatively and qualitatively than the StK technique and similar image quality compared to ASIR30%.…”
Section: Image Noise Image Contrast Artifactsmentioning
confidence: 99%
“…Various studies have reported the benefits of using ASiR techniques in the abdomen, the chest, coronary CT angiography, the head and cervical spine. 7,12,14,15,26,27 ASiR allows the use of a higher scanner NI, which helps in reducing the tube current and radiation exposure. 12,14,15 In the present study, the NI could be increased by 27% after implementation of ASiR in CT scan of patients with blunt cervical spine trauma.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 ASiR transforms repeatedly the pixel Hounsfield values of an image until they converge on a final value by using matrix algebra. 12 Noise is inversely proportional to the square root of dose. By lowering image noise, this method allows tube current reduction, thus decreasing radiation dose, with recovery of image quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations